2007
DOI: 10.1037/0033-295x.114.3.806
|View full text |Cite|
|
Sign up to set email alerts
|

Resolving the IQ paradox: Heterosis as a cause of the Flynn effect and other trends.

Abstract: IQ test scores have risen steadily across the industrialized world ever since such tests were first widely administered, a phenomenon known as the Flynn effect. Although the effect was documented more than 2 decades ago, there is currently no generally agreed-on explanation for it. The author argues that the phenomenon heterosis represents the most likely cause. Heterosis, often referred to as hybrid vigor, is a genetic effect that results from matings between members of genetically distinct subpopulations, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 97 publications
0
65
1
13
Order By: Relevance
“…It has been hypothesized that genetic mean increases due to outbreeding (hybrid vigor) is an important contributor to the Flynn effect [44,45]. We consider it plausible that outbreeding has resulted in increases in genetic means.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that genetic mean increases due to outbreeding (hybrid vigor) is an important contributor to the Flynn effect [44,45]. We consider it plausible that outbreeding has resulted in increases in genetic means.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in non-human animals, cross-bred dairy cows gain weight faster and produce more milk (Cundiff et al 1974) and cross-bred dogs are more successful in guide dog training (Ennik et al 2006). In humans, heterosis has been suggested to be linked to factors such as early growth (Penrose 1955;Wolanski et al 1970) and some authors have suggested that increase in IQ may be linked to heterosis (Mingroni 2007). Such arguments might suggest that mixed-ethnicity faces may be attractive because such individuals have different appearing faces (eg healthier, more symmetric, etc) because individuals with a diverse set of genes are able to develop or maintain attractive traits.…”
Section: Introductionmentioning
confidence: 99%
“…However, many interspecific hybrids suffer from reduced longevity and reductions in fertility. Heterosis in humans has been proposed, sometimes controversially, to affect multiple phenotypes including attractiveness [1], IQ [2,3], and height [4][5][6]. In agricultural settings, there are numerous examples in which heterosis has been harnessed to create more productive and more uniform products including livestock [7][8][9][10][11] and crop plants (reviewed in [12][13][14][15][16][17][18][19]).…”
Section: Introductionmentioning
confidence: 99%